Incidence, predictors and impact of stroke on mortality among patients with acute coronary syndromes following percutaneous coronary intervention—Results from the PROMETHEUS registry. Issue 5 (14th June 2019) - Chandiramani, Rishi; Chen, Huazhen; Aoi, Shunsuke; Giustino, Gennaro; Claessen, Bimmer; Sartori, Samantha; Aquino, Melissa; Sorrentino, Sabato; Cao, Davide; Goel, Ridhima; Kini, Annapoorna; Rao, Sunil; et al.
Abstract: Background: Stroke represents a potentially calamitous complication among patients with acute coronary syndrome (ACS) undergoing percutaneous intervention (PCI). Data on the distribution of stroke occurrence post‐PCI and its impact on mortality are scarce. Objectives: We sought to determine the incidence, predictors and impact of stroke on mortality in ACS patients undergoing PCI. Methods: A total of 19, 914 ACS patients underwent PCI in the PROMETHEUS multicenter observational study. We calculated the cumulative stroke incidence at 30 days and 1 year using the Kaplan Meier method. We also compared the distribution of stroke, myocardial infarction (MI), and bleeding across time and evaluated their overlap. Predictors of stroke were identified through multivariable Cox‐regression. Stroke, MI, and bleeding were assessed as time‐updated covariates to estimate how each impacts subsequent mortality. Results: We found that 244 patients had a stroke within 1 year, a cumulative incidence of 1.5%. Previous cerebrovascular disease was the strongest predictor for post‐PCI stroke, followed by ST‐elevation MI presentation, hypertension, non‐ST‐elevation MI presentation, smoking, female sex, and age. Mortality risk was significantly higher among those who had a stroke versus those who did not (adjusted HR 4.84, p < .0001). However, the association attenuated over time with a much larger effect in the first 30 days of its occurrence (adjusted HR 17.7; 95% CI: 12.3–25.4, p < .0001) versus beyond 30 days (adjusted HR 1.22; 95% CI: 0.6–2.46, p = .58). Conclusions: Stroke occurrence within 1 year was not uncommon for ACS patients undergoing PCI. When compared with MI and bleeding, stroke had a substantial impact on mortality that attenuated rapidly over time.